Transitions between subclasses of bullying and victimization when entering middle school. Issue 1 (9th September 2013) - Williford, Anne; Boulton, Aaron J.; Jenson, Jeffrey M.
Abstract We examined the effects of depressive symptoms, antisocial attitudes, and perspective‐taking empathy on patterns of bullying and victimization during the transition from late elementary (4th grade to 5th grade) to middle school (6th grade) among 1, 077 students who participated in the Youth Matters (YM) bullying prevention trial. Latent transition analysis was used to establish classes of bullying, victimization, bully‐victimization, and uninvolvement. The intervention had a positive impact on children as they moved from elementary to middle school. More students in the YM group transitioned from the involved statuses to the uninvolved status than students in the control group during the move to middle school. Elementary school bullies with higher levels of depressive symptoms were less likely than other students to move to an uninvolved status in the first year of middle school. Students who held greater antisocial attitudes were more likely to be a member of the bully‐victim status than the uninvolved status during the move to middle school. Perspective‐taking empathy, however, was not a significant predictor of status change during the transition to middle school. Implications for school‐based prevention programs during the move to middle school are noted. Aggr. Behav. 40:24–41, 2014. © 2013 Wiley Periodicals, Inc.